The effect of physical contact on changes in fatigue markers following rugby union field-based training. Issue 6 (3rd July 2017) - Roe, Gregory; Darrall-Jones, Joshua; Till, Kevin; Phibbs, Padraic; Read, Dale; Weakley, Jonathon; Rock, Andrew; Jones, Ben
Abstract: Repeated physical contact in rugby union is thought to contribute to post-match fatigue; however, no evidence exists on the effect of contact activity during field-based training on fatigue responses. Therefore, the purpose of this study was to examine the effect of contact during training on fatigue markers in rugby union players. Twenty academy rugby union players participated in the cross-over study. The magnitude of change in upper- and lower-body neuromuscular function (NMF), whole blood creatine kinase concentration [CK] and perception of well-being was assessed pre-training (baseline), immediately and 24 h post-training following contact and non-contact, field-based training. Training load was measured using mean heart rate, session rating of perceived exertion (sRPE) and microtechnology (Catapult Optimeye S5). The inclusion of contact during field-based training almost certainly increased mean heart rate (9.7; ±3.9%) and sRPE (42; ±29.2%) and resulted in likely and very likely greater decreases in upper-body NMF (−7.3; ±4.7% versus 2.7; ±5.9%) and perception of well-being (−8.0; ±4.8% versus −3.4; ±2.2%) 24 h post-training, respectively, and almost certainly greater elevations in [CK] (88.2; ±40.7% versus 3.7; ±8%). The exclusion of contact from field-based training almost certainly increased running intensity (19.8; ±5%) and distance (27.5; ±5.3%), resulting in possibly greater decreases in lower-body NMF (−5.6; ±5.2% versus 2.3; ±2.4%). Practitioners should be aware of the different demands and fatigue responses of contact and non-contact, field-based training and can use this information to appropriately schedule such training in the weekly microcycle.